Prevalence of trematode Metacercariae in Cyprinoid fish and food consumption behaviors of people from Chiang Rai Province, Northern Thailand - Jitkham, P.; Wongsawad, C.; Koychusakun, P.; Phalaraksh, C. (International Journal of Agricultural Technology, 2020)
The prevalence of trematode metacercariae in cyprinoid fish and food consumption behaviors of local people from Nong Luang wetland area, Chiang Rai Province, Northern Thailand were investigated. The fish samples were collected from Nong Luang wetland between April and December 2016. The total number of 11 trematode species from 360 cyprinoid fish samples were identified. The prevalence rate of metacercaria in cyprinoid fishes was 39.17% which mostly found from Henicorhynchus siamensis 100% (7/7), Systomus rubripinnis 94.44% (17/18), Barbonymus gonionotus 76.74% (33/43), Rasbora tornieri 55.56% (5/9), Osteochilus vittatus 50% (1/2), Puntius brevis 30.39% (31/102), Anematichthys repasson 28.95% (33/114), Luciosoma bleekeri 25% (3/12), Labiobarbus siamensis 21.57% (11/51). The highest number of metacercaria identified from this study was Haplorchoides spp. followed by Centrocestus formosanus. Moreover the findings revealed that seasonal changes relatively affected to the prevalence of metacercaria in cyprinoid fishes. The highest prevalence of metacercaria can be found in winter season. The residents of Nong Luang Wetland had a moderate level of raw fish consumption behaviors (95.8%). However, the result shows that the residents of Nong Luang Wetland consume raw or half cooked fish according to easy cooking. The health education of appropriate fish consumption and the risk of liver fluke were recommened to transfer to the residents and local government of Nong Luang wetland area.